Wiener Chaos Expansion for Fatigue Damage Approximation of an FPSO Mooring Chain - Yarveisy, Rioshar (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2015)
The impact of fatigue damage on design of FPSO position mooring systems and specifically slender structure load carrying equipment e.g. mooring chains, wire ropes, synthetic fiber ropes and etc. has changed during the past few decades. The service location of FPSO vessels has moved from shallow water to deep and ultra-deep waters. In case of shallow water mooring systems (except for north Atlantic like environments) strength based design will most likely meet the fatigue requirements. On the other hand in case of deep-water station keeping operations fatigue is becoming the dominant factor in design of mooring systems. This matter asks for development and introduction of more reliable and accurate toolsets and approaches to provide effective, economical and reliable solutions in the future. The aim of this study is to first investigate the accuracy of different spectral fatigue estimation methods in comparison with expected fatigue damage using rainflow counting of stress cycles. Then two long term fatigue approximation methods, Wiener chaos expansion and Gaussian approximation, are implemented. Wiener chaos expansion is thought to be the solution to a variety of problems. On the other hand utilizing the Gauss approximation formula for this application is considered to be common practice. Here the aim is to compare the two mentioned long-term approximative methods with short-term estimation of fatigue damage i.e. direct rainflow counting and spectral models. Another aspect of the present project is the employed commercial software package DeepC. The software is a time domain coupled analysis toolbox used to extract the force time series on mooring lines.